2017
DOI: 10.3390/e19080412
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Entropy, Corporate Entrepreneurship and Organizational Capabilities in Romanian Medium Sized Enterprises

Abstract: This paper analyses the relations between entropy, organizational capabilities and corporate entrepreneurship. The results indicate strong links between strategy and corporate entrepreneurship, moderated by the organizational capabilities. We find that companies with strong organizational capabilities, using a systematic strategic approach, widely use corporate entrepreneurship as an instrument to fulfil their objectives. Our study contributes to the limited amount of empirical research on entropy in an organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 74 publications
(81 reference statements)
0
14
0
3
Order By: Relevance
“…Given the factors of corporate entrepreneurship, ample literature is available on the antecedents that foster it, like leaders (Zahra 1996). Transformational leadership has been recognized by several scholars as one of the significant antecedents for promoting employees' corporate entrepreneurship (Ceptureanu et al 2017;Chang et al 2017). Because it involves being passionate about innovation and converting firms' turbulent business environment into business opportunity (Avolio et al 2004;Howell and Higgins 1990), transformational leadership is thought to encourage their employees to frequently adapt and expect environmental transformation through entrepreneurial activities (Su and Baird 2017;Waldman et al 2004).…”
Section: Corporate Entrepreneurshipmentioning
confidence: 99%
“…Given the factors of corporate entrepreneurship, ample literature is available on the antecedents that foster it, like leaders (Zahra 1996). Transformational leadership has been recognized by several scholars as one of the significant antecedents for promoting employees' corporate entrepreneurship (Ceptureanu et al 2017;Chang et al 2017). Because it involves being passionate about innovation and converting firms' turbulent business environment into business opportunity (Avolio et al 2004;Howell and Higgins 1990), transformational leadership is thought to encourage their employees to frequently adapt and expect environmental transformation through entrepreneurial activities (Su and Baird 2017;Waldman et al 2004).…”
Section: Corporate Entrepreneurshipmentioning
confidence: 99%
“…On the one hand, particularly for smaller companies, it is crucial to build networks in foreign markets to overcome entry barriers. On the other hand, one of the cornerstones of international business theory is the possession of intangible assets as a foundation for international competitiveness [55][56][57].…”
Section: The Moderating Effects Of Organizational Capabilities In Legmentioning
confidence: 99%
“…Using the data of listed companies on the Korea Stock Exchange, they showed that excess human resources and financial flexibility could be used for additional non-financial information disclosure, such as the publication of CSR, sustainability, and integrated reports. Information processing capabilities of executives was investigated in Ceptureanu et al [30]. Table 1 shows the attributes and levels used in the choice experiment.…”
Section: Literature Reviewmentioning
confidence: 99%